The Effectiveness of the Reading to Learn (R2L) Model on Scientific Literacy Skills on Static Electricity Topic - Khairil Arif; Olyivia Retdwina Rusma; Aulia Musva Putri; Firda Azzahra (Postgraduate, University of Mataram, 2023)
The purpose of this study was to determine the difference in science learning outcomes between groups of students who participated in learning with the Reading to Learn (R2L) model and direct learning, by analyzing the literacy skills of class IX students at Junior High School in Bukittinggi, West Sumatra. The study population was all students of class IX and the sample class was selected by purposive sampling technique, so that class IX-6 was obtained as the experimental group and class IX-4 as the control group, with a sample of 56 students. This research is a quasi-experimental research with a pretest and posttest group design pattern. The data collected is a test of learning outcomes which are analyzed quantitatively to measure students' scientific literacy skills which are grouped into 3 aspects, namely numerical, conceptual, and multidimensional aspects. The instrument used is a scientific literacy test in the form of 10 description questions. The results show that the research hypothesis H1 is accepted because the table shows that t count > t table. This hypothesis test found that the application of the Reading to Learn (R2L) approach had an effect on students' scientific literacy skills. While the results of the experimental group N-Gain was 0.44 or 44% in the medium category (less effective). So we look at some of the factors causing it by giving questionnaires to students. Based on statistical calculations, the scores for each indicator in the questionnaire are 87.5% of students using local languages in daily conversation, reading time of 10-30 minutes is 46.88%, and courses or tutoring outside school hours are 28.13%.